Primes and Their Connection to Certain Polyhedral Number Sequences - Benjamin Lee Warren (Journal of Mathematics)
A collection of results is given regarding whether a prime can be the sum or difference of two polyhedral numbers, as well as some primality restrictions on several sequences.